2019
DOI: 10.1111/mbe.12194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pointing Gestures on Memory for (In)Congruent Stimuli in Children and Young Adults

Abstract: We investigated whether finger pointing toward picture locations can be used as an external cognitive control tool to guide attention and compensate for the immature cognitive control functions in children compared with young adults. Item and source memory performance was compared for picture‐location pairs that were either semantically congruent (e.g., a cloud presented at the upper half of the screen) or incongruent (e.g., a cloud presented at the lower part of the screen). Contrary to our expectations, poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…For example, Guillaume et al (2020) showed that incongruent information's recognition benefit elicited more positive waveforms than congruent information. In contrast, studies by Feyereisen (2009) and Ouwehand et al (2019) highlighted a memory advantage for congruent information. Such findings suggest that the enhanced memory for congruent information may arise from schema facilitation during encoding (Ouwehand et al, 2019;van Kesteren et al, 2013).…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…For example, Guillaume et al (2020) showed that incongruent information's recognition benefit elicited more positive waveforms than congruent information. In contrast, studies by Feyereisen (2009) and Ouwehand et al (2019) highlighted a memory advantage for congruent information. Such findings suggest that the enhanced memory for congruent information may arise from schema facilitation during encoding (Ouwehand et al, 2019;van Kesteren et al, 2013).…”
Section: Introductionmentioning
confidence: 75%
“…In contrast, studies by Feyereisen (2009) and Ouwehand et al. (2019) highlighted a memory advantage for congruent information. Such findings suggest that the enhanced memory for congruent information may arise from schema facilitation during encoding (Ouwehand et al., 2019; van Kesteren et al., 2013).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations